2018
DOI: 10.1016/j.ejpb.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the dried product resistance variability and its influence on the product temperature in pharmaceutical freeze-drying

Abstract: During the primary drying step of the freeze-drying process, mass transfer resistance strongly affects the product temperature, and consequently the final product quality. The main objective of this study was to evaluate the variability of the mass transfer resistance resulting from the dried product layer (R) in a manufacturing batch of vials, and its potential effect on the product temperature, from data obtained in a pilot scale freeze-dryer. Sublimation experiments were run at -25 °C and 10 Pa using two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
5
20
0
Order By: Relevance
“…It is well-known that dried product resistance and product temperature increase when product dried layer thickness increases. 19,22,36 Therefore, to include the maximum effect of the dried product resistance during the determination of the sublimation rate, the sublimation experiments were stopped once the dried layer of the front edge vials was close to the vial bottom. This was performed by visually observing the dried layer of the front edge vials.…”
Section: Determination Of Sublimation Ratementioning
confidence: 99%
“…It is well-known that dried product resistance and product temperature increase when product dried layer thickness increases. 19,22,36 Therefore, to include the maximum effect of the dried product resistance during the determination of the sublimation rate, the sublimation experiments were stopped once the dried layer of the front edge vials was close to the vial bottom. This was performed by visually observing the dried layer of the front edge vials.…”
Section: Determination Of Sublimation Ratementioning
confidence: 99%
“…It has been reported that the resistance of the dried product increases as the length of the dried layer of the product increases (Fissore et al, 2011;Kodama et al, 2014;Kuu et al, 2006;Scutellà et al, 2018b). This implies that the sublimation rate decreases by increasing the product dried layer.…”
Section: Determination Of Sublimation Ratementioning
confidence: 99%
“…where is the the mass transfer resistance of the dried layer, which depends linearly on the dried layer thickness for the considered product: [7] = 0 + 1 (5) can be calculated from the Clausius Clapeyron equation from the sublimation interface temperature, [6] and is defined as in Trelea et al [8] assuming ideal gas law for water vapour in the drying chamber:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…This phenomenon is known as edge vial effect. In the present study, the additional radiation heat flow rates from the wall and rail to the edge vials were calculated for edge vials using the Stefan-Boltzmann equation, as proposed in the 3D simplified radiation model developed by Scutellà et al [10]  Mass transfer resistance: The product resistance variability in a large batch of vials was previously quantified as normal distributions of 0 and 1 in Scutellà et al [7]  Desorption kinetics: The variability of the desorption kinetics was previously quantified as normal distributions of characteristics desorption times in Scutellà et al [11]…”
Section: Heat and Mass Transfer Variability In Freeze-dryingmentioning
confidence: 99%